Деформационно-энергетические аспекты и примеры практического применения процесса сварки взрывом - Лысак, В.И.; Кузьмин, С.В. (Автоматическая сварка, 2008)
Deformation-energy aspects of explosion welding processes have been analyzed. The established functional correlation between the parameters of this process in combination with the developed mathematical models, enables controlling the energy and temperature-time conditions in the joint zone and formation of the required structure and properties in the produced composite materials. Examples of effective application of explosion welding are given.